Peran Teman Sebaya Terhadap Siswa Slow Learner - Salma Belva Calysta (Jurnal Humaniora & Sosial Sains, 2025)
This study examines the important role of peers in supporting slow learners in inclusive schools, based on a qualitative case study in a public junior high school. Inclusive education, which aims to integrate regular students with Children with Special Needs (ABK), faces challenges in its social practices. Observations revealed significant gaps, with slow learners experiencing limited interaction and minimal social acceptance from their classmates. The study subjects were often seen alone, excluded from group activities, and did not receive adequate academic or emotional support when facing learning difficulties. These findings confirm that the presence of ABK in regular classes does not automatically create an inclusive environment. Peer support is a key factor that has not yet been realized, even though their role is vital as a bridge to foster empathy, self-confidence, and social success in students with ABK. Therefore, active intervention from schools is needed to build a culture of caring and collaboration among students.